If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + 8)(2y + 8) = 0 Reorder the terms: (8 + 2y)(2y + 8) = 0 Reorder the terms: (8 + 2y)(8 + 2y) = 0 Multiply (8 + 2y) * (8 + 2y) (8(8 + 2y) + 2y * (8 + 2y)) = 0 ((8 * 8 + 2y * 8) + 2y * (8 + 2y)) = 0 ((64 + 16y) + 2y * (8 + 2y)) = 0 (64 + 16y + (8 * 2y + 2y * 2y)) = 0 (64 + 16y + (16y + 4y2)) = 0 Combine like terms: 16y + 16y = 32y (64 + 32y + 4y2) = 0 Solving 64 + 32y + 4y2 = 0 Solving for variable 'y'. Factor out the Greatest Common Factor (GCF), '4'. 4(16 + 8y + y2) = 0 Factor a trinomial. 4((4 + y)(4 + y)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(4 + y)' equal to zero and attempt to solve: Simplifying 4 + y = 0 Solving 4 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + y = 0 + -4 y = 0 + -4 Combine like terms: 0 + -4 = -4 y = -4 Simplifying y = -4Subproblem 2
Set the factor '(4 + y)' equal to zero and attempt to solve: Simplifying 4 + y = 0 Solving 4 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + y = 0 + -4 y = 0 + -4 Combine like terms: 0 + -4 = -4 y = -4 Simplifying y = -4Solution
y = {-4, -4}
| 30p-11p+15p-29p=90 | | -6+2(5-4x)=22-2x | | -6(-2x+2)+4(3+4x)=28 | | 10xt=1.8654 | | (a+6)(a^2-8a+8)=0 | | 6m^2+66m+121=0 | | 3.0=0.4m-2+0.2m | | 8w-3w-4w-1=32 | | (7y)^1/3 | | 10xt= | | 5x+10+x=-8 | | (5x+3)(2x-6)=0 | | px^2+qx+r=(x+1)(2x-7) | | 3x-2=x*x | | 3s-2s-1=29 | | 79=-7k | | 34/36 | | -29j+35j-(-39)=-33 | | (2x-2)(4x-7)=0 | | X/6-x/8=9 | | 3√7/9x2 | | 5y-8=8-4y-4 | | 12=-3(2-2r)-(2r+2) | | -2x(x^2+4x-5)=0 | | 35t-25t+10t-16t-3=49 | | 20=6x^2-7x | | x^y-^/x-4^y3^ | | 35k+7k-37k-k-3k+2=24 | | 4u+v-9u+18v= | | 3^sqrt7/9x^2 | | -26=-4(5-5n)-6(n-6) | | 43z-41z+5z=49 |